Simultaneous Bilateral Reconstruction of the Axilla with Posterior Arm Flap in Recurrent Hidradenitis Suppurativa - M., Kingsly Paul; Ete, Geley; J., Felix Cordelia M.; Akamanchi, Anirudha K.; Agarwal, Shwetha (Indian Journal of Plastic Surgery, 2022)
Introduction Hidradenitis suppurativa (HS) is a chronic inflammatory disease, with the axilla being the most commonly affected site. Radical excision of the involved tissue is a definitive treatment. There are numerous techniques described for the reconstruction of the axilla.Patients and methods Patients with axillary HS who underwent wide excision and posterior arm flap cover between August 2017 and December 2020 were reviewed.Results A total of 15 flaps were done in eight patients in the study period. Bilateral radical excision of the disease was done simultaneously in all eight patients with the help of a two-team approach. Reconstruction of the axilla was done with a posterior arm flap bilaterally, except one side in a single patient, wherein the split-thickness skin graft was performed. All flaps settled well without significant complications. On follow-up ranging from 12 to 42 months, one patient complained of disease recurrence on one side. The flap and the donor site had settled well in all patients, causing no significant morbidity.Conclusion Radical excision of axillary hidradenitis must be considered early on presentation. After wide excision, simultaneous bilateral reconstruction with posterior arm flap is a simple and reliable technique with an excellent patient-reported outcome.
Keywords: Hidradenitis suppurativa; Radical excision; Axilla reconstruction; Posterior arm flap